Four decades of soil moisture decline: a remote sensing analysis of southern ñeembucú, Paraguay (1983-2023) - Arévalos Vera, Porfirio Domingo; Pereira, Walter Esfrain (JRG Journal of Academic Studies, 2024)
The objective of this research is to analyze the evolution of soil moisture in the southern region of Ñeembucú Department from 1983 to 2023, utilizing remote sensing data and geospatial processing techniques, as well as to evaluate soil moisture trends at different depths (0 to 290 cm). The focus is on changes that have occurred over the last four decades in an area characterized by wetlands. The selected area covers a total surface of 6,636.499 km2, encompassing the districts of Pilar, Humaitá, Paso de Patria, General Díaz, Mayor Martínez, Isla Umbú, Desmochados, Guazu Cuá, Tacuaras, Villalbín and Laureles. Remote sensing data and geospatial processing techniques were employed, using image collections from "NASA/FLDAS/NOAH01/C/GL/M/V001" and "ECMWF/ERA5_LAND/MONTHLY_AGGR" from Google Earth Engine, filtered for the study area. Variables of interest included soil water content in layers: 0-10 cm, 10-40 cm, 40-100 cm and 100-200 cm, and 0-7 cm, 7-28 cm, 28-100 cm and 100-289 cm, respectively. It was verified generalized decrease in soil moisture across all layers, most pronounced in surface layers. Deeper layers experienced a more gradual reduction. In conclusion, the southern region of Ñeembucú has experienced a consistent reduction in soil moisture over the past four decades, attributed to both climatic and anthropogenic factors. This study highlights the urgent need to adopt mitigation measures and sustainable management practices to preserve ecosystems and ensure long-term water resource availability.